Fungsi Pengawasan Terhadap Keselamatan Penerbangan Bandara Udara (Studi Di Bandara Udara Kuabang Kao. Kab. Halmahera Utara) - Tabaru, Makswel Y; Rumapea, Patar; Tampongangoy, Deysi (Sam Ratulangi University, 2016)
ABSTRACT :To serve takeoff (departure) and landing aircraft (arrival) air is provided runway (run way).Takeoff or take-offs and landings are landing. The road connecting the runway to the apron. Apron is theaircraft parking area after landing and drop off passengers and luggage, further examination of aircraftengines, refueling (aviation fuel) into the air, then loading the luggage and waiting for passengers boardingan aircraft.This study dilakasanakan at the Airport Kuabang Kao northern Halmahera regency. This type of research iscategorized as research Kualitatif. Data retrieval in the form of primary data and secondary data, interviewsand images as well as air service profile Kuabang Kao northern Halmahera district. The results of the studymengunakandata results of research conducted during one month with a focus on the issue of aviation safetyoversight of airports Kao northern Halmahera district. Based on the findings in the study site activities at theairport penerbangann kaoefektit but not efisenya of government supervision. Based on data Pantawanconducted by researchers at the airport kao used as a farm business between the government and the airportof the proof when asked by the interview data sejaumana government's attention to airports kao, according toan employee of the airport that the airport has a lot of projects but no realizationKeywords: Supervision of Aviation Safety Air Kao